2016
DOI: 10.5430/jnep.v6n12p63
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a summer extern program on nursing student’s awareness of interprofessional collaboration and healthy, healing environments: A level II quasi-experimental design

Abstract: Background: Student nurse externships bridge the gap between education and practice. These programs expose students to the interprofessional healthcare team, the work environment and its impact on themselves as well as their patients. Methods: Research Objective/Questions: 1) What is the nurse externs' knowledge of a healthy healing environment (HHE) at the beginning of an 8 week summer externship program? 2) How does participation in the interprofessional externship inform the externs' knowledge and awareness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The results from the participant questionnaires validated previous literature regarding healthy work environments. 4 These externs noted that interprofessional collaboration is a key component in a healthy work environment. Furthermore, externs gained an appreciation of how quality interprofessional collaboration positively impacts teamwork which improves the work environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from the participant questionnaires validated previous literature regarding healthy work environments. 4 These externs noted that interprofessional collaboration is a key component in a healthy work environment. Furthermore, externs gained an appreciation of how quality interprofessional collaboration positively impacts teamwork which improves the work environment.…”
Section: Discussionmentioning
confidence: 99%
“…Externships, very similar to the transition-to-practice residency programs, align with clinical immersion experiences to reinforce safe patient care, clinical reasoning, and holistic decision-making 4,5. When students are immersed in the clinical environment through externships, real-life opportunities are presented that benefit students' knowledge which is essential for the new, novice nurse's survival in today's complex healthcare arena 4,5…”
Section: Externship Benefits and Challengesmentioning
confidence: 99%
“…To the knowledge of the authors, the impacts of prelicensure clinical extern programs on humanistic caring (or related concepts such as empathy and compassion) have rarely been reported. Indeed, the outcomes mostly revolve around students benefits such as confidence and clinical skills ( Rugs et al, 2020 ), interprofessional collaboration ( Ruth-Sahd, 2016 ), professionalism, job satisfaction, and sense of belonging ( Cantrell et al., 2005 ), transition into the professional nurse role ( Cantrell & Browne, 2005 ) in addition to recruitment and retention ( Cantrell & Browne, 2006 ; Friday et al., 2015 ; Remle et al, 2014 ). However, two studies ( Massé, 2016 ; Oja, 2013 ) reported a development of communication skills in externs who completed their program.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies highlight improvement in professional values, knowledge base, teamwork skills, and overall self-confidence from experiences as SNEs (Shipman et al, 2016; White et al, 2019b). Ruth-Sahd (2016) also found that participation in externships fostered interprofessional collaboration and promoted a smoother transition to professional practice. Wilkerson and Faber (2015) noted outcomes of improving recruitment and easing the transition from education to the hospital work environment as well as boosting retention through externships.…”
mentioning
confidence: 87%
“…Summer nurse externships provide prelicensure students with the opportunity to work in a registered nurse (RN)-supervised position and function like a nurse while under the direction of nursing faculty (Rugs et al, 2020; White et al, 2019b). Goals of externships are to increase acute care clinical exposure, build critical thinking skills, and foster networking and relationships between the student nurse extern (SNE) and RN role models (Ruth-Sahd, 2016). Externships provide opportunities for students typically entering the final 6–12 months of their academic program to practice skills, clinical decision-making, delegation, and prioritization (White et al, 2019a).…”
mentioning
confidence: 99%